Phonon- and electron-temperature waves in a Maxwell-Cattaneo heat-conduction theory. Issue 1 (6th October 2020) - Sellitto, A.
Abstract: A two-temperature model, which is fully compatible with the Maxwell-Cattaneo heat-conduction theory, is developed. It allows to account for different heat carriers' temperatures, as well as for their mutual energy exchange. Its physical consistency is proved by means of the second law of thermodynamics. The propagation of phonon- and electron-temperature waves is also analyzed, and the results are plotted in the case of a Bi 2 Te 3 sample at 300 K .